2009
DOI: 10.1016/j.nutres.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate dietary magnesium intake increases atherosclerotic plaque development in rabbits

Abstract: Epidemiological studies have shown dietary magnesium (Mg) intake and serum Mg levels to be inversely correlated with the development of atherosclerosis. We hypothesized that low levels of Mg would promote atherosclerotic plaque development in rabbits. New Zealand white rabbits (4 months old, n = 22) were fed an atherogenic diet containing 0.12% (−Mg), 0.27% (control), or 0.43% (+Mg) Mg for 8 weeks. Blood samples were obtained at baseline, 2, 4, 6, and 8 weeks and were assayed for total cholesterol, high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
(50 reference statements)
3
31
0
1
Order By: Relevance
“…The rabbits had been on a special fatty diet. 23 The basal diet contained 10% fat, 1% cholesterol, 0.11% Mg, 14% protein and 54% carbohydrates (Catalog No. 1811279, 5TZB, Purina Test Diet, Richmond, IN).…”
Section: B Liver Samplesmentioning
confidence: 99%
“…The rabbits had been on a special fatty diet. 23 The basal diet contained 10% fat, 1% cholesterol, 0.11% Mg, 14% protein and 54% carbohydrates (Catalog No. 1811279, 5TZB, Purina Test Diet, Richmond, IN).…”
Section: B Liver Samplesmentioning
confidence: 99%
“…The rabbits had been on a special fatty diet. 41 The basal diet contained 10% fat, 1% cholesterol, 0.11% Mg, 14% protein, and 54% carbohydrates (Catalog No. 1811279, 5TZB, Purina Test Diet, Richmond, IN).…”
Section: B Liver Samplesmentioning
confidence: 99%
“…There is, furthermore, much evidence that hypomagnesaemia also plays a signi fi cant role in the pathogenesis of cardiovascular diseases and that a high serum magnesium level may retard the development and/or acceleration of arterial calci fi cation and, subsequently, atherosclerosis in ESRD patients. Many experimental studies in animal models have clearly shown a relationship of low Mg with vascular calci fi cation and atherosclerotic lesions [ 96,[112][113][114] .…”
Section: Arterial Calci Fi Cations Atherosclerosismentioning
confidence: 99%